Design, synthesis and aggregation induced emission properties of two bichromophores with a triphenylamine-coumarin dyad structure. (November 2017) - Yan, Han; Meng, Xinlei; Li, Baoyan; Ge, Shusheng; Lu, Yun
Abstract: On the basis of molecular design about the donor-acceptor (D-A) triphenylamine-coumarin (TPA-coumarin) dyad, two new bichromophores 7-butoxy-6-(4-(diphenylamino)phenyl)-4, 8-dimethyl-2 H -chromen-2-one (TC ) and 7-butoxy-6-(4-(diphenylamino)phenyl)-8-methyl-4-(trifluoromethyl)-2 H -chromen-2-one (TF ), were synthesized and characterized by using IR, 1 H NMR, 13 C NMR and HRMS. BothTC andTF exhibited the expected solid-state fluorescence emission due to the aggregation induced emission effect and different degrees of positive solvatochromism due to their different molecular conformations in various solvents. Owing to the different push-pull electronic effects of substituents on the coumarin moiety, TC andTF, acting as the D-A compounds, showed different HOMO-LUMO gaps and a variable red-shifted emission in their solid-state, substantiating the possibility to effectively tune the photophysical properties of these bichromophores by rational molecular design. Graphical abstract: